An Analysis of Passengers’ Safety Risk at the Infrastructure Improvement Project of Railway Station - Nanda Ahda Imron; Dian M Setiawan; Ali Oktavian Handoko; Erifendi Churniawan; Handoko Handoko; Ary Putra Iswanto (Journal of Railway Transportation and Technology, 2022)
Constructing the elevated track at the Manggarai Railway Station has risk which potentially endangers the passengers’ safety due to its construction process is carried out within passengers’ activities around the railway station. This research aims to identify the hazard and risks, analyze the level and control the risk. Moreover, this study also aims to arrange the priority of serial alternative solutions regarding the handling the risk within the construction process of elevated track. This study used methods as follows: Hazard Identification, Risk Assessment, And Risk Control (HIRARC) and Analytical Hierarchy Process (AHP). In addition, data triangulation was also done by involving three respondents in keeping with to ensure the validity. The analysis of HIRARC generated 11 hazards and risks namely 6 are classified into extreme risks, 4 are rated high risk and 1 is categorized as medium risk. The method of AHP is used to analyze the alternative ways of handling the risks and to find out the priorities above some alternative ways of handling the risks. The sequence of the alternative ways of handling the risks based on the top priority is as follows: (1) first priority by applying the switch over 5, (2) second priority by adding the KLB feeder, (3) third priority by increasing the service facility.